Analisis Kinerja Anggaran Desa Pada Lembang Rantebua Kecamatan Sanggalangi Kabupaten Toraja Utara - Fitri Banne; Dwibin Kannapadang; Ade Lisa Matasik (Politeknik Kampar, 2024)
This research is a qualitative research. This research discusses the analysis of Village Budget Performance in Lembang Rantebua, Sanggalangi District, North Toraja Regency. The aim of this research is to find out how well the village fund budget is performing in Lembang Rantebua, Sanggalangi District, North Toraja Regency. The data collection techniques used were interviews and documentation. The data analysis technique used is the effectiveness ratio and efficiency ratio. Based on the results of the analysis, it is stated that the Financial Performance of Lembang Rantebua, Sanggalangi' District, North Toraja Regency, when viewed from the effectiveness ratio, is categorized as effective, because the average effectiveness from 2019-2022 is 95.31% and the Financial Performance of Lembang Rantebua, Sanggalangi District, North Toraja Regency if Judging from the efficiency ratio, it is categorized as less efficient, because the average efficiency from 2019-2022 is 88.65%.